2015
DOI: 10.1016/j.bbrc.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of Sirt6 in the crosstalk among ageing, metabolic syndrome and osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disorder commonly associated with metabolic syndrome. As ageing and obesity has a great impact on the initiation/severity of OA, herein we sought to investigate the involvement of Sirt6 in the crosstalk between ageing and metabolic syndrome/OA. Sirt6 haploinsufficiency in mice promoted the expression of inflammatory cytokines in the IPFP. Enhanced inflammation of the IPFP in the aged Sirt6 ± HFD group was paralleled with accelerated OA change, including osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Following consumption of a high‐fat diet, expression levels of mRNA for all of these cytokines were enhanced in wild‐type and SIRT‐6 +/− mice, with IL‐6 mRNA expression further enhanced in SIRT‐6 +/− mice . Moreover, SIRT‐6 +/− mice exhibited accelerated cartilage degradation when fed a normal diet, and they displayed greater osteophyte formation and synovial inflammation when fed a high‐fat diet . These results suggest that impaired SIRT‐6 links metabolic dysfunction with multiple aspects of OA, including cartilage degradation, synovial inflammation, and bone remodeling.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Following consumption of a high‐fat diet, expression levels of mRNA for all of these cytokines were enhanced in wild‐type and SIRT‐6 +/− mice, with IL‐6 mRNA expression further enhanced in SIRT‐6 +/− mice . Moreover, SIRT‐6 +/− mice exhibited accelerated cartilage degradation when fed a normal diet, and they displayed greater osteophyte formation and synovial inflammation when fed a high‐fat diet . These results suggest that impaired SIRT‐6 links metabolic dysfunction with multiple aspects of OA, including cartilage degradation, synovial inflammation, and bone remodeling.…”
Section: Introductionmentioning
confidence: 89%
“…Since dysregulation of AMPK and SIRTs is seen in experimental animal models of obesity and metabolic syndrome, AMPK and SIRTs could be critical mediators in the cross-talk between dysregulated metabolic tissues, such as adipose tissue and joint tissues. 16 BERENBAUM ET AL A recent study showed significantly increased expression of messenger RNA (mRNA) for inflammatory cytokines and adipokines, including TNF, IL-6, and leptin, in the infrapatellar fat pad of SIRT-6 haploinsufficient (SIRT-6 1/2 ) mice compared to wild-type mice (89). Following consumption of a high-fat diet, expression levels of mRNA for all of these cytokines were enhanced in wildtype and SIRT-6 1/2 mice, with IL-6 mRNA expression further enhanced in SIRT-6 1/2 mice (89).…”
Section: Berenbaum Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Genome‐wide DNA methylation changes have been shown in hip and knee cartilage in human osteoarthritis patients and have been linked to differential expression of 70 genes, including the osteoarthritis‐associated genes VIT , ROR2 , and WLS . Altered activity of the Sirtuin family of histone deacetylases, in particular SIRT1, SIRT3, and SIRT6, has also been implicated in arthritis . In particular, increased histone acetylation within articular cartilage has been linked to ectopic hypertrophy in the mouse knee, including increased expression of matrix metalloproteases (e.g., MMP‐13) that degrade joint cartilage …”
Section: Developmental Pathways In Adult Joint Diseasementioning
confidence: 99%
“…Ailixiding et al sought to investigate the role of SIRT6 in the crosstalk between aging and metabolic syndrome/OA and therefore used a SIRT6 haploinsufficient mouse 18 . Feeding these mice a HFD resulted in a significantly higher blood glucose level in the SIRT6 haploinsufficient mice compared to control mice, indicating susceptibility to metabolic syndrome.…”
Section: Sirt6mentioning
confidence: 99%